The physiological aspect of thyroid-induced breast cancer: a case report - Putu Austin Widyasari Wijaya (Intisari Sains Medis, 2020)
Background: Breast cancer has the second-highest prevalence of cancer in Indonesia. The aetiology of breast cancer involves endogenous sex hormone activity, estrogen. Besides, thyroid hormones have estrogen-like effects on breast tissue which are thought to play a role in the development of breast cancer. This case report aims to evaluate the physiological aspect of thyroid-induced breast cancer.Case Report: A 49-year-old Balinese woman came to the Primary Health Care with a history of uncontrolled hyperthyroidism for 5 years (2014-2019), complaining of a lump in her left breast. Open biopsy and immunohistochemistry were done (Grade III Invasive Carcinoma ER + 50%, Her + 2-3). Patients were diagnosed with stage 3B breast cancer and conservative treatment has been taken. The examination of TSH thyroid hormone was 0.204 µIU/mL (normal = 0.5 - 6 µIU/mL) and FT4 3.1 ng/dL (normal = 0.7-1.9 ng/dL).The primary management of patients was chemotherapy following by Modified Radical Mastectomy (MRM), hormone suppressant injection, as well as Herceptin. Those medications were effective in reducing the development of breast cancer through thyroid hormone pathway.Conclusion: Some studies showed hyperthyroidism increase the risk of breast cancer and that high thyroid levels can cause estrogen-like effects, trigger proliferation and angiogenesis by activating the same pathway as estrogen those are mitogen-activated protein kinase (MAPK) and extracellular signal-regulated kinase ½ (ERK ½).